Metabolic trajectories of diabetic ketoacidosis onset described by breath analysis - Awchi, Mo; Singh, Kapil Dev; Brenner, Sara Bachmann; Burckhardt, Marie-Anne; Hess, Melanie; Zeng, Jiafa; Datta, Alexandre N.; Frey, Urs; Zumsteg, Urs; Szinnai, Gabor; Sinues, Pablo (Frontiers in Endocrinology, 2024)
This feasibility study aimed to investigate the use of exhaled breath analysis to capture and quantify changes of metabolites during resolution of acute diabetic ketoacidosis under insulin and rehydration therapy. This feasibility study aimed to investigate the anabolic effect of insulin on metabolites captured in exhaled breath during acute diabetic ketoacidosis (DKA), with the goal of enhancing our understanding of the pathophysiological impact of insulin and rehydration therapy initiation on DKA treatment and recovery.This feasibility study aimed to investigate the anabolic effect of insulin on metabolites captured in exhaled breath during acute diabetic ketoacidosis (DKA) for a better pathophysiological understanding.Breath analysis was conducted on 30 patients of which 5 with DKA. They inflated Nalophan bags, and its their metabolic content was subsequently interrogated by secondary electrospray ionization high-resolution mass spectrometry (SESI-HRMS).SESI-HRMS analysis showed that acetone, pyruvate, and acetoacetate, that which are well known to be altered in DKA, were readily detectable in breath of participants with DKA. In addition, a total of 665 mass spectral features were found to significantly correlate with base excess and prompt metabolic trajectories towards an in-control state as they progress towards homeostasis.This study provides proof-of-principle for using exhaled breath analysis in a real ICU setting for DKA monitoring. This non-invasive new technology provides new insights and a more 34 comprehensive overview on of the effect of insulin and rehydration during DKA treatment.